2020
DOI: 10.1180/clm.2020.38
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid nanocomposites of elastomeric polyurethane containing halloysite nanotubes and POSS nanoparticles: tensile, hardness, damping and abrasion performance

Abstract: Thermoplastic polyurethane (TPU) matrix was reinforced with polyhedral oligomeric silsesquioxane (POSS) and halloysite nanotubes (HNT), both separately and combined. Composite samples were fabricated using a melt-compounding method. Characterization of the composites obtained was performed via tensile and hardness tests, melt-flow index measurements (MFI), abrasion tests, dynamic mechanical analysis (DMA) and scanning electron microscopy (SEM) to investigate the mechanical performance, flow behaviour, tribolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 132 publications
1
5
0
Order By: Relevance
“…It can be observed that increasing the HNT level improved the Shore D hardness of TPU/HNT nanocomposite dog-bone samples from 71.50 (TN1) to 76.67 (TN17), as shown in Figure 7 a, which could be related to embedded HNTs to obstruct hydrogen bonding between polymeric segments with the formation of new hydrogen bonds between HNTs and TPU molecular chains [ 25 ]. It has been proven that the inherent hardness and stiffness of nanofillers makes it possible to enhance the hardness of corresponding nanocomposites, as reported by Mohamed et al [ 52 ] when preparing TPU/2 wt% HNT composites for corrosive coating application.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that increasing the HNT level improved the Shore D hardness of TPU/HNT nanocomposite dog-bone samples from 71.50 (TN1) to 76.67 (TN17), as shown in Figure 7 a, which could be related to embedded HNTs to obstruct hydrogen bonding between polymeric segments with the formation of new hydrogen bonds between HNTs and TPU molecular chains [ 25 ]. It has been proven that the inherent hardness and stiffness of nanofillers makes it possible to enhance the hardness of corresponding nanocomposites, as reported by Mohamed et al [ 52 ] when preparing TPU/2 wt% HNT composites for corrosive coating application.…”
Section: Resultsmentioning
confidence: 99%
“…Diminishing the total tensile strength of it. The increase in hardness can be attributed to the improved packing density of the polymer matrix 50 . When fillers are introduced, they occupy the spaces between polymer chains, resulting in a reduction in free volume and facilitating closer packing of the polymer molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in hardness can be attributed to the improved packing density of the polymer matrix. 50 When fillers are introduced, they occupy the spaces between polymer chains, resulting in a reduction in free volume and facilitating closer packing of the polymer molecules. This closer packing enhances the load transfer mechanism within the material, reducing localized deformation and maintaining the structural integrity of the polymer.. 19,51 Consequently, the hardness of the TPU composite increases.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…This could be explained by the fact that more crosslinks formed in the greater filler loading, increasing the crosslink density. Better dispersion and distribution of HNTs along with the interaction of van der Waals and hydrogen bonds may be responsible for the increased tensile strength with more force required to break the specimens 46 . The strong interfacial interaction between the HNTs and the rubber matrix, as well as the even dispersion of the HNTs, allow for efficient load transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Better dispersion and distribution of HNTs along with the interaction of van der Waals and hydrogen bonds may be responsible for the increased tensile strength with more force required to break the specimens. 46 The strong interfacial interaction between the HNTs and the rubber matrix, as well as the even dispersion of the HNTs, allow for efficient load transfer. The high aspect ratio of the HNTs provides a larger contact area with the matrix, enhancing the load-bearing capacity resulting in improved tensile strength.…”
Section: Recovery Of Tensile Propertiesmentioning
confidence: 99%